Techno-economical evaluation of coupling ionizing radiation and biological treatment process for the remediation of real pharmaceutical wastewater. (1st January 2020) - Changotra, Rahil; Rajput, Himadri; Guin, Jhimli Paul; Khader, Shaik Abdul; Dhir, Amit
Abstract: Pharmaceutical manufacturing industries produce a vast range of substances by using organic and inorganic compounds as raw material thereby gives rise to huge volume of toxic and complex organic liquid effluents comprised of high levels of dissolved solids. High and low strength wastewater streams originating from manufacturing unit often contains different types of contaminants, including organic compounds which can be difficult to treat with conventional methods of treatment. In this study, the sequential treatment process of coagulation, electron beam (E-beam) irradiation and biological treatment was employed on real pharmaceutical industrial wastewater to study the impact of combined treatment on remediation and detoxification of the wastewater. Combined treatment was performed on low (LOSW ) and high (HOSW ) organic strength wastewater collected from representative pharmaceutical industry. Operational parameters like pH, absorbed dose and use of oxidants were systematically investigated to achieve the enhanced treatment of wastewater streams using E-beam irradiation. Biological treatment was carried out using activated sludge process at laboratory-scale reactor by utilizing acclimatized consortia in the experiments. Sequential hybrid coagulation, E-beam irradiation and biological treatment lead to synergistic degradation and detoxification of both the recalcitrant wastewater streams with overall chemical oxygen demand (COD) removal of 94% and 89% for LOSW and HOSW, respectively. Cytotoxicity assessment revealed that the combined treatment of wastewater was effective in eliminating the toxicity when tested against the selected microorganisms. The treatment cost of E-beam radiolysis alone, biological treatment alone and E-beam + biological treatment for LOSW was found to be 0.50, 2.35 and 2.85 USD m −3 ; whereas, for HOSW, it was found to be 0.67, 0.7 and 1.37 USD m −3, respectively. The overall cost of the set-up of an E-beam unit and the treatment cost for real pharmaceutical wastewater was evaluated to establish the applicability of the E-beam technology at industrial scale. The feasibility of E-beam irradiation for wastewater remediation may ensure future smart cities with sustainable resource management. Graphical abstract: Image 1 Highlights: Sequential coagulation, electron beam and biological treatment of real pharmaceutical wastewater. Aerobic biological degradation experiments were performed in laboratory scale activated sludge process reactor. Effective degradation and detoxification of wastewater using combined treatment. Overall cost assessment of electron beam induced treatment of wastewater.